The Effect of Using Different Competence Frameworks to Audit the Content of a Masters Program in Public Health - Harrison, Roger A.; Gemmell, Isla; Reed, Katie (Frontiers in Public Health, 2015)
Objectives (1) To quantify the effect of using different public health competence frameworks to audit the curriculum of an online distance learning MPH programme, and (2) to measure variation in the outcomes of the audit depending on which competence framework is used. Study Design Retrospective audit Methods We compared the teaching content of an online distance learning MPH programme against each competence listed in different public health competence frameworks relevant to an MPH. We then compared the number of competences covered in each module in the programme’s teaching curriculum and in the programme overall, for each of the competence frameworks used in this audit. Results A comprehensive search of the literature identified two competence frameworks specific to MPH programmes and two for public health professional/specialty training. The number of individual competences in each framework was 32 for the taught aspects of the UK Faculty of Public Health Specialist Training Programme, 117 for the American Association of Public Health, 282 for the exam curriculum of the UK Faculty of Public Health Part A exam, and 393 for the European Core Competencies for MPH Education. This gave a total of 824 competences included in the audit. Overall, the online MPH programme covered 88% to 96% of the competences depending on the specific framework used. This fell when the audit focused on just the three mandatory modules in the programme, and the variation between the different competence frameworks was much larger. Conclusions Using different competence frameworks to audit the curriculum of an MPH programme can give different indications of its’ quality, especially as it fails to capture teaching considered to be relevant yet not included in an existing competence framework. The strengths and weaknesses of using competence frameworks to audit the content of an MPH programme has largely been ignored. These debates are vital given that external organisations responsib